Clinical Impact of Preoperative Biliary Drainage in Patients with Ductal Adenocarcinoma of the Pancreatic Head - Amaral, Maria João (2023)
Our aim was to study the association between preoperative biliary drainage (PBD) and morbidity following cephalic pancreaticoduodenectomy (CPD) for pancreatic ductal adenocarcinoma (PDAC) and its prognostic impact, which is still controversial in the literature. A retrospective study was conducted, which included 128 patients who underwent CPD for PDAC, divided into two groups: those who underwent PBD (group 1) and those who did not undergo this procedure (group 2). Group 1 was subdivided according to the drainage route: endoscopic retrograde cholangiopancreatography (ERCP), group 1.1, and percutaneous transhepatic cholangiography (PTC), group 1.2. 34.4% of patients underwent PBD, and 47.7% developed PBD-related complications, with 37% in group 1.1 and 64.7% in group 1.2 (p = 0.074). There was a significant difference between group 1 and 2 regarding bacterial colonization of the bile (45.5% vs. 3.6%, p < 0.001), but no difference was found in the colonization by multidrug-resistant bacteria, the development of Clavien-Dindo ≥ III complications, clinically relevant pancreatic fistula and delayed gastric emptying (DGE), intra-abdominal abscess, hemorrhage, superficial surgical site infection (SSI), and readmission. Between groups 1.1 and 1.2, there was a significant difference in clinically relevant DGE (44.4% vs. 5.9%, p = 0.014) and Clavien-Dindo ≥ III complications (59.3% vs. 88.2%, p = 0.040). There were no significant differences in median overall survival and disease-free survival (DFS) between groups 1 and 2. Groups 1.1 and 1.2 had a significant difference in DFS (10 vs. 5 months, p = 0.017). In this group of patients, PBD was associated with increased bacterial colonization of the bile, without a significant increase in postoperative complications or influence in survival. ERCP seems to contribute to the development of clinically significant DGE. Patients undergoing PTC appear to have an early recurrence.